Flood Hazard Spatialization Applied to The City of Batna: A Methodological Approach - Harkat, N.; Chaouche, S.; Bencherif, M. (Engineering, Technology & Applied Science Research, 2020)
Flood flows can cause destruction to properties and infrastructure or even cost human lives. Batna is an Algerian city that is highly exposed to the risk of flooding, with an average of one flood every three to four years. The current methods utilized to analyze flood hazards are limited to the hydrology of the watershed. Limiting the analysis of flood hazards could mislead the decision-makers from proper management of such risks. The objective of the current study is to propose a simplified flood hazard model called HEC RAS-DTM (Hydrologic Engineering Centers River Analysis System (HEC RAS)-Digital Terrain Model (DTM)) and to evaluate it utilizing data gathered from the hydrological context and the hydraulic modeling of Batna city. The model entails two distinct phases. Initially, it attempts to use descriptive statistical methods based mainly on frequency analysis, which consists of studying flood flows in order to determine the probability of future flood occurrence. The analysis of the hydrological context of the city of Batna has revealed that peak flows from stream floods have been predicted at various return periods. Subsequently, HEC RAS was deployed to produce hydraulic modeling in order to extract the water heights and speeds corresponding to these expected flows. These data, along with DTM, are crucial for the spatialization of flood hazards. The hydraulic modeling and simulation using HEC-RAS and Geographic Information System (ArcGIS) of water flow at the two main valleys, Oued Batna and Oued El Gourzi, allowed predicting the extent of flooding that could occupy a large part of the city. The mapping of the flood hazard revealed the sectors that would be most exposed. The results obtained from the suggested model confirm that a significant portion of the city of Batna remains vulnerable to floods in relevance with the predicted flood return periods. The suggested model has indicated significant growth in flood locality. Additionally, the model was proved to be efficient for the analysis of flood flows, and it could easily substitute conventional analysis methods. Further studies or investigations are advised in order to replicate the study in different contexts. The article entails suggestions for properly managing flood risks. Future studies on flood risk alleviation in Batna city could be likewise considered.